Transregionalism: Problems of Terminology and Conceptualization - D. A. Kuznetsov (Сравнительная политика, 2016)
Today’s world is witnessing the remarkable development of transregional ties between distinct regions and powers within the international system evolving towards multipolarity. However, the essence of transregionalism remains understudied to the extent that there is no clear consensus for which terminology should be used to define this phenomenon. The article compares existing approaches to transregionalism conceptualization, analyzes the differences in the use of terms, and discusses the global impact of transregional relations on world politics and economy. The author advocates a term transregionalism (instead of interregionalism, crossregionalism, macroregionalization etc.) and suggests its definition.